Predicting Social Adjustment Based on the Ability to Solve Social Problems and Selfcompassion in Adolescents - Sara Arshi (Shiraz University of Medical Sciences, 2022)
Background: This study aimed to predict social adjustment based on the ability to solve social problems and self-compassion in adolescents. Methods: This is a cross-sectional study. The statistical population of this study includes all high school students in Shiraz in 2018. The statistical sample consisted of 800 students (400 girls and 400 boys) selected by random cluster sampling. The author used questionnaires of the California Social Adjustment Test, Self-Compassion Scale, and Short Form of Social Problem-Solving Questionnaire (SPSI-R: SF) to collect information from the sample group. Results: There is a positive and significant relationship between social adjustment and the ability to solve social problems (r = 0.23, P <0.01). Also, there is a positive and significant relationship between social adjustment and self-compassion (r = 0.017, P <0.01). Regression coefficients indicate that problem-solving ability (P = 0.34) and self-compassion (P = 0.30) can positively and significantly predict social adjustment and problem-solving ability has a stronger role in explaining social adjustment than self-compassion. Conclusion: Problem-solving training was used as an effective way to create general, emotional, social, and educational adjustment of adolescents. People who have a high problem-solving ability can control their stress in normal and stressful situations.